Implementasi Sistem Reverse Osmosis Dengan Sumber Listrik Tenaga Surya Untuk Menyediakan Air Siap Minum Di Pondok Pesantren Al-Karimiyyah Desa Braji, Kabupaten Sumenep - Dewantara, Belly Yan; Sugiarto, Erik; Yusan, Liza Yudistira; Trisyani, Ninis (Jurnal Pengabdian Masyarakat Pesisir, 2024)
This activity aims to improve water quality through the implementation of the Reverse Osmosis system, a water filtration process that neutralizes taste, odor, and harmful substances present in water, making it suitable for drinking. One of the challenges faced by Al-Karimiyyah Islamic Boarding School, located in Braji Village, Gapura District, Sumenep Regency, is its heavy reliance on traditional water management methods and the use of bottled water services, which require significant manpower, time, and incur high costs. Therefore, the implementation of a water purification system utilizing Reverse Osmosis technology is crucial to provide readily available drinking water. This system will be placed outdoors for easy access by the students. Solar panel technology will be employed as the primary source of power, allowing the system to be self-sustained and placed in any location. Through this Community Engagement Activity, the solar-powered Reverse Osmosis system presents an alternative solution for providing safe drinking water, thereby streamlining costs and time spent. Moreover, it offers educational benefits by raising awareness among students about the importance of consuming clean water to prevent illnesses